Islamic Energy Garden: A shariah-based approach to achieve a ‘Green and Barakah Campus’ - Madihah Mat Idris; Magda Sibley; Elina Mohd Husini; Nasrudin Sharkawi; Fadli Arabi; Azman Ab. Rahman (e-IPH Ltd., 2025)
Indexed